IOT based Automatic Street Light Control and Fault Detection - et. al., Prashant Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The IoT (Internet of Things) is a blooming technology that mainly concentrates on the interconnection of devices to one another and the people. The world is getting smarter these days, and people are drawn to the word "Smart". Given that India is one of the world's fastest-growing tech markets, we are incorporating a smart framework into the switch. The project's goal is to provide automatic control and fault detection for street light. The lights are switched ON/OFF automatically based on the intensity of sunlight using the LDR sensor. Automation helps to solve a variety of challenges in both the global economy and everyday life. The power supply which is supplied to the system is converted via Relay before supplying to the street lights. Here the system check’s fault in the street light and also sends the alert message to the authorized mobile number through the GSM module. An object's motion is detected using an infrared sensor. According to the program, if there is any object comes near the IR sensor, the light will glow as bright. Otherwise, the light will glow as dim.